Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Certainly! Let's solve the equation step-by-step.
Given the equation:
[tex]\[ 0.25(4F - 3) = 0.05(10F - 9) \][/tex]
### Step 1: Simplify both sides of the equation
First, distribute the constants on both sides.
For the left side:
[tex]\[ 0.25(4F - 3) = 0.25 \cdot 4F - 0.25 \cdot 3 \][/tex]
[tex]\[ = 1F - 0.75 \][/tex]
[tex]\[ = F - 0.75 \][/tex]
For the right side:
[tex]\[ 0.05(10F - 9) = 0.05 \cdot 10F - 0.05 \cdot 9 \][/tex]
[tex]\[ = 0.5F - 0.45 \][/tex]
### Step 2: Set the simplified equations equal to each other
Now, equate the simplified expressions:
[tex]\[ F - 0.75 = 0.5F - 0.45 \][/tex]
### Step 3: Combine like terms to solve for [tex]\( F \)[/tex]
To isolate [tex]\( F \)[/tex], we first eliminate the terms involving [tex]\( F \)[/tex] from one side:
[tex]\[ F - 0.5F = 0.75 - 0.45 \][/tex]
[tex]\[ 0.5F = 0.3 \][/tex]
### Step 4: Solve for [tex]\( F \)[/tex]
Finally, divide both sides of the equation by 0.5 to solve for [tex]\( F \)[/tex]:
[tex]\[ F = \frac{0.3}{0.5} \][/tex]
[tex]\[ F = 0.6 \][/tex]
### Conclusion
The solution to the equation [tex]\( 0.25(4F - 3) = 0.05(10F - 9) \)[/tex] is:
[tex]\[ F = 0.6 \][/tex]
Given the equation:
[tex]\[ 0.25(4F - 3) = 0.05(10F - 9) \][/tex]
### Step 1: Simplify both sides of the equation
First, distribute the constants on both sides.
For the left side:
[tex]\[ 0.25(4F - 3) = 0.25 \cdot 4F - 0.25 \cdot 3 \][/tex]
[tex]\[ = 1F - 0.75 \][/tex]
[tex]\[ = F - 0.75 \][/tex]
For the right side:
[tex]\[ 0.05(10F - 9) = 0.05 \cdot 10F - 0.05 \cdot 9 \][/tex]
[tex]\[ = 0.5F - 0.45 \][/tex]
### Step 2: Set the simplified equations equal to each other
Now, equate the simplified expressions:
[tex]\[ F - 0.75 = 0.5F - 0.45 \][/tex]
### Step 3: Combine like terms to solve for [tex]\( F \)[/tex]
To isolate [tex]\( F \)[/tex], we first eliminate the terms involving [tex]\( F \)[/tex] from one side:
[tex]\[ F - 0.5F = 0.75 - 0.45 \][/tex]
[tex]\[ 0.5F = 0.3 \][/tex]
### Step 4: Solve for [tex]\( F \)[/tex]
Finally, divide both sides of the equation by 0.5 to solve for [tex]\( F \)[/tex]:
[tex]\[ F = \frac{0.3}{0.5} \][/tex]
[tex]\[ F = 0.6 \][/tex]
### Conclusion
The solution to the equation [tex]\( 0.25(4F - 3) = 0.05(10F - 9) \)[/tex] is:
[tex]\[ F = 0.6 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.